[Howard Louis' Scrapbook, 1927-1933] - Howard Louis::::::::: (1926)
Scrapbook created by Howard "Toby" Louis, between 1926 and 1932, primarily during his time at San Luis High school and college at U.C. Berkeley. Includes photos of friends and family, including Fred Louis, Ah Louis (Wong On), Helen Louis, Elsie Louis, and the Louis and Watson families. Includes photographs of track and field, football, and other athletic events. Includes photographs of trips to Yosemite, the Ah Louis Store, and local Central Coast trips.